Thalictrum peruvianum (Ranunculaceae), a new species from Lima, Peru - Trinidad, Huber (2011)
A new species, Thalictrum peruvianum H. Trinidad & A. Cano (Ranunculaceae), is described from central Peru. It is characterized for having very small and solitary flowers that born opposite to the leaves, and by winged stigma. These characters distinguish this new taxon from other South American species.